Islamic Ethical Identity Scorecard; a Combination of Shari’ah Screening, Ethical Identity Index and Corporate Social Responsibility Screening Dimensions - Adedokun, Balqis Oyindamola (2016)
Screening exercise adopted by Islamic commercial institutions has several repeated and redundant dimensions. The aim of this study is to create an Islamic Ethical Identity Scorecard with limited dimensions, inculcating Shari’ah screening, Ethical Identity Index (EII) and Corporate Social Responsibility (CSR) criteria required by Islamic investors. The Islamic Ethical Identity Scorecard also fills the gap in the current inconsistency problem of Shari’ah screening by adopting the strategies proposed by (Derigs & Marzban, 2009) for arriving at a harmonized screening requirement. This study employed analytical processual analysis and developed eight dimensions important to Islamic investors. The creation of limited dimensions is expected to ease the process companies go through in fulfilling the expectations of investors interested in Islamic assets; thereby increasing the percentage of Shari’ah compliant companies and the growth of Islamic investments. Furthermore, the study tests the level of companies’ compliance to the new model. Using a sample of 200 companies approved by SAC as at May 29, 2015, the study found that only 19% of SAC approved companies comply with the requirements of the scorecard. The main reason for non-compliance was high debt ratio especially from capital intensive industries.